EFFECT OF FURNISH COMPOSITION (LONG FIBER, BCTMP, AND FILLER) ON DEWATERING PERFORMANCE AND PAPER QUALITY - Moehammad Djoedie Setiawan; I.G.B. Ngurah Makertihartha (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study analyzes the effect of fiber composition and filler type on drainage behavior in papermaking and its relationship with forming dewatering and paper properties. The furnish consisted of Short Fiber (SF), Long Fiber (LF), and Bleached Chemi-Thermomechanical Pulp (BCTMP), while fillers included Ground Calcium Carbonate (GCC) and Precipitated Calcium Carbonate (PCC) at various ratios. Drainage time (s/500 mL) was used as a laboratory indicator and correlated with forming dewatering performance. Results show that increasing BCTMP proportion accelerates drainage, indicated by shorter drainage times and lower forming dewatering values, reflecting faster water removal and a drier web. The fastest drainage time was 15.68 s/500 mL under PCC-dominated conditions (85%). In contrast, increasing LF from 10% to 30% increases flow resistance, resulting in longer drainage times (up to 20.8 s/500 mL) and higher forming dewatering values, indicating slower dewatering and a wetter web. Filler type significantly influences drainage behavior. Higher GCC content, due to its finer particles, increases flow resistance through pore blocking, leading to higher forming dewatering values. Conversely, PCC promotes more stable permeability and faster dewatering. In terms of paper properties, higher BCTMP increases bulk and thickness while slightly reducing density, whereas LF improves strength, with internal bond increasing from 235 to 309 J/m² and tensile strength reaching 4.35 N. These results confirm that furnish composition is critical in balancing dewatering rate and web moisture, which is essential for stable machine operation and consistent paper quality.